1965
DOI: 10.2466/pr0.1965.16.3.877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recall Condition, Presentation Rate and Retention Interval on Short-Term Memory

Abstract: A total of 300 university students were presented a brief list of non-alphanumeric items and instructed to recall immediately either the items (free recall, FR), the order in which the items were presented (order recall, OR), or both (serial recall, SR). Presentation rate and retention interval were additional experimental variables in Exp. I and II, respectively. In both experiments significant differences in recall were found between FR conditions and the remaining two, which did not differ from each other. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1967
1967
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…If there is any effect of time, it is a tendency toward improved recall after 30 sec, an effect similar to that described as reminiscence (Peterson, 1966). The findings of the present experiment are generally consonant with the few other studies presenting data on one-trial recall in short term memory (Goggin, 1966;Keppel " Underwood, 1962;Rohrman" Jahnke, 1965). It is difficult to see how a trace view could be made con-sonant with such data unless the trace decay process is hypothesized as operating under conditions not met by the present experiment but which have obtained in other short term memory experiments.…”
Section: Discussionsupporting
confidence: 90%
“…If there is any effect of time, it is a tendency toward improved recall after 30 sec, an effect similar to that described as reminiscence (Peterson, 1966). The findings of the present experiment are generally consonant with the few other studies presenting data on one-trial recall in short term memory (Goggin, 1966;Keppel " Underwood, 1962;Rohrman" Jahnke, 1965). It is difficult to see how a trace view could be made con-sonant with such data unless the trace decay process is hypothesized as operating under conditions not met by the present experiment but which have obtained in other short term memory experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In a one-trial-one-test experiment of the sort reported here, retention interval per se leads to no significant memory loss and offers no support for a trace decay view of STM. This generalization seems to be consonant with the reports from other studies in the literature reporting one-trial data (Goggin, 1966;Keppel & Underwood, 1962;Rohrman & Jahnke, 1965).…”
Section: Discussionsupporting
confidence: 89%
“…Though open to interpretation, like Conrad's (1965) experiment, there does appear to be a good deal of evidence which seems most reasonably interpreted in favor of the independence of item information and order information. Rohrman and Jahnke (1965), Zimmerman and Underwood (1968), and Experiments I and II reported here have all shown that requiring 5s to recall order information has no effect on the amount of item information recalled. These findings might be explained as they were by Zimmerman and Underwood; that is, order information is an obligatory attribute and 5s always learn order information when they learn item information.…”
Section: Resultsmentioning
confidence: 45%
“…One of the efforts to separate these various factors was made in an experiment by Rohrman and Jahnke (1965) in which they attempted to determine if item and order information were subject to different processes. After presentation of a single list, 5s recalled either item, order, or item and order information.…”
mentioning
confidence: 99%
See 1 more Smart Citation